Religion, Terrorism and Weapons of Mass Destruction: Expediters or Hindrances for Global Peace - Ghada Awada (Randwick International of Social Science Journal, 2020)
The purpose of the study was to examine the validity of the argument indicating that the religious nature of the terrorist groups accounts for the increase in the violence of terrorist acts today. The study also intended to explore the relationship between terrorism and religion and to address whether or not there has been interrelatedness between religion and terrorism. Another purpose was to explore the scope of Weapons of Mass Destruction (WMD) and to examine how religion was exploited to disseminate terrorism and eradicate global peace and how the possession of WMD could influence global peace. The study employed a meta-analysis of literature which pointed out the significance of religion and the controversy as to whether or not religion triggered terrorist violence. Incidents such as 9/11, the 2005 London underground attack, Paris attack, and 2019 attack in New Zealand were analyzed to serve the purposes of the study. The findings showed the main triggers and incentives behind the terrorist attacks waged in the name of religion. Overall, the findings of the study emphasized the influence of religion on terrorism, and vice versa. The study rendered conclusions that delved into infamous attacks and recognized terrorism as caused by religion or perceptions fogged by media and stereotypes.